Perancangan Web Blogger sebagai Media Promosi pada UMKM Prima Catra - Mia Nurlita; Natasya Felisha; Novi Ardi Winata; Novadilastri; Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This research discusses the importance of online marketing for micro, small and medium enterprises (MSMEs) in the digital era, with a focus on Prima Catra MSMEs in Padang City. In this research, the interview method was used to collect information from business owners. The results show that Prima Catra has great potential in meeting printing service needs, but has not yet utilized the digital platform optimally. By developing blogs as promotional media, it is hoped that these MSMEs can increase their competitiveness in the market. This project is also part of the Project Based Learning (PBL) activities of Business Administration Study Program students, which aims to provide practical experience in designing websites.